Retention of placenta in she camel (Camelus dromedarius) - ROHILLIA, NAVNEET; SINGH, UMED (The Indian Journal of Animal Reproduction, 2023)
A case ofretention of placenta rare of its kind has been reported in she camel.
Keywords: Retention; placenta; camel